Engaging Italy : American women's utopian visions and transnational networks - Madden, Etta M., 1962- (Albany : State University of New York Press, 2022)
"Traces literary and social connections among three American women navigating the changing political landscape of 1860s and '70s Italy"--
Brewster's Life Alone: Utopian and Dystopian Visions -- Chapter 10 Caroline Crane Marsh: "The Power of Doing a Great Service" -- Surrogate Motherhood: The Power and Service of Letting Go -- Serving Schools: Fundraising at Home and Abroad -- Transformations of a Reformer and Litterateur -- "In Vain Have I Labored": Ideas of Italian Reform Revised -- Coda: Residual Ripples -- Hidden Lives & Unvisited Tombs -- Appendix A: "To ____ ____." -- Appendix B: "For Queen Anne" -- List of Abbreviations -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 29, 2022).
JSTOR
Keywords: Women -- Italy -- History -- 19th century; Americans -- Italy -- History -- 19th century; Italy -- Politics and government -- 1849-1870.; Femmes -- Italie -- Histoire -- 19e siècle.; Italie -- Politique et gouvernement -- 1849-1870.; LITERARY CRITICISM / Women Authors; Americans; Politics and government; Women; Italy; 1800-1899; History; Literary criticism; Critiques littéraires.